THE INFLUENCE OF FINANCIAL LITERACY ON THE QUALITY OF ECONOMIC DECISION MAKING AMONG URBAN COMMUNITIES - Fajri, Heri; Mariana, Mariana; Kusumo, Yudhy Widya; Abral, Edi; Alfianti, Julia (UNIVERSITAS NEGERI SURABAYA, 2025)
To make wise financial decisions, especially amid the complexity of today's financial situations, financial literacy encompassing knowledge, skills, and confidence is crucial. Financial literacy is an essential ability in urban environments, where the economic dynamics are highly complex. This study examines how financial literacy influences the ability of urban residents to make wise financial decisions. A quantitative approach was used with a survey of 200 individuals with stable incomes, from the upper middle class in Lhokseumawe City, aged between 25 and 55 years. Purposive sampling was used to choose the sample. The questionnaire measured the quality of economic decision-making and financial literacy (knowledge, skills, and confidence) using a 5-point Likert scale. To analyze the relationships between variables, multiple linear regression, descriptive statistics, t-tests, and F-tests were applied. The findings showed that the regression model Y = 0.298 + 0.223X1 - 0.096X2 + 0.766X3 + ϵ illustrates the relationship between dependent and independent variables. Financial knowledge significantly improves the quality of economic decision-making (t-statistic 6.292, p = 0.000). Financial skills negatively affect economic decision-making (t-statistic -3.258, p = 0.001). Confidence significantly positively influences decision-making (t-statistic 18.947, p = 0.000). The F-test revealed an F-value of 244.043 with p = 0.000, confirming the significant impact of independent variables on the quality of economic decision-making. These findings highlight the importance of knowledge and confidence in economic decisions, while incorrect financial skills may pose risks.